Financial Dependence and International Trade - Beck, Thorsten (World Bank, Washington, DC, 2014)
Does financial development translate into a comparative advantage in industries that use more external finance? The author uses industry-level data on firms' dependence on external finance for 36 industries and 56 countries to examine this question. The author shows that countries with better-developed financial systems have higher export shares and trade balances in industries that use more external finance. These results are robust to the use of alternative measures of external dependence and financial development and are not due to reverse causality or simultaneity bias.